Persepsi Pemuda Terhadap Pekerjaan di Sektor Pertanian (Studi Kasus Desa Timpag, Kerambitan, Tabanan) - Yosafat Jala Tana; I Made Tamba; I Made Sukerta (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
This research was conducted in Timpag Village, Kerambitan, Tabanan. The number of samples in this study were 30 people with the Quota sampling method. Data collection techniques using the method of observation, interviews, documentation, literature study and questionnaires. The analysis technique used is the Chi Square analysis method. Based on the results of the analysis it was found that the results of the youth's perception of employment in the agricultural sector of Timpag Village as a whole were negative. Of the 30 respondents, the majority stated that they had negative perceptions of work in the agricultural sector as many as 21 people (70%), while 9 people (30%) had positive perceptions of work in the agricultural sector. This is due to the young people who are respondents are young people who are looking for work with vocational / high school education equivalent and Bachelor degree. It is also caused by the family background of the youth who no longer come from family farmers and do not have agricultural land. all the factors tested do not have a relationship with youth perceptions of employment in the agricultural sector. Youth will have a negative perception of agricultural work when they do not have the skills or expertise in the agricultural sect